2010
DOI: 10.3310/hta14080
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination and publication of research findings: an updated review of related biases

Abstract: How to obtain copies of this and other HTA programme reports An electronic version of this title, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable DVD is also available (see below).Printed copies of HTA journal series issues cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our despatch agents.Non-UK purchasers will have to pay a small fee for post and packing. For Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
704
2
13

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 821 publications
(730 citation statements)
references
References 213 publications
(332 reference statements)
11
704
2
13
Order By: Relevance
“…Finally, testing for funnel plot asymmetry was not performed as only seven studies were included in this review [37] . We acknowledge that reporting bias may lead to over-representation of significant or positive studies [38] .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, testing for funnel plot asymmetry was not performed as only seven studies were included in this review [37] . We acknowledge that reporting bias may lead to over-representation of significant or positive studies [38] .…”
Section: Discussionmentioning
confidence: 99%
“…Language of publication(s). 367 (88) 25 (6) 27 (6) 259 (62) Single-centre study 159 (38) 1 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) 129 (81) 16 (10) 14 (9) 158 (99) Multi-centre study 260 (62) 1 238 (92) 9 (3) 13 (5) 101 ( perceived as an overestimation of the publication proportion. We excluded conference abstracts and other so-called 'grey literature' because those publications are often not indexed in electronic databases (in particular, abstracts of smaller conferences).…”
Section: Discussionmentioning
confidence: 99%
“…• Publication or dissemination bias-Several systematic reviews of empirical studies have found that clinical trials with statistically significant (P<0.05) or positive results are more likely to be published than those with non-significant or negative results (39)(40)(41). Investigators' decisions not to submit papers with negative results for publication, rather than editors' rejection of such papers, tend to be the main source of publication bias (42).…”
mentioning
confidence: 99%
“…However, the decision to write up a study for publication may be influenced by pressure from study sponsors and journal editor (25). Studies with statistically significant results also tend to be published earlier than studies with non-significant results (40). If studies are missing from a systematic review for these reasons, exaggerated results may be produced.…”
mentioning
confidence: 99%